Nitrogen-Efficient and Nitrogen-Inefficient Indian Mustard Showed Differential Expression Pattern of Proteins in Response to Elevated CO2 and Low Nitrogen - Yousuf, Peerzada Y.; Ganie, Arshid H.; Khan, Ishrat; Qureshi, Mohammad I.; Ibrahim, Mohamed M.; Sarwat, Maryam; Iqbal, Muhammad; Ahmad, Altaf (Frontiers in Plant Science, 2016)
Carbon (C) and nitrogen (N) are two essential elements that influence plant growth and development. The C and N metabolic pathways influence each other to affect gene expression, but little is known about which genes are regulated by interaction between C and N or the mechanisms by which the pathways interact. In the present investigation, proteome analysis of N-efficient and N-inefficient Indian mustard, grown under varied combinations of low-N, sufficient-N, ambient [CO2] and elevated [CO2] was carried out to identify proteins and the encoding genes of the interactions between C and N. Two-dimensional gel electrophoresis (2-DE) revealed 158 candidate protein spots. Among these, 72 spots were identified by matrix-assisted laser desorption ionization-time of flight/time of flight mass spectrometry (MALDI-TOF/TOF). The identified proteins are related to various molecular processes including photosynthesis, energy metabolism, protein synthesis, transport and degradation, signal transduction, nitrogen metabolism and defense to oxidative, water and heat stresses. Identification of proteins like PII-like protein, cyclophilin, elongation factor-TU, oxygen-evolving enhancer protein and rubisco activase offers a peculiar overview of changes elicited by elevated [CO2], providing clues about how N-efficient cultivar of Indian mustard adapt to low N supply under elevated [CO2] conditions. This study provides new insights and novel information for a better understanding of adaptive responses to elevated [CO2] under N deficiency in Indian mustard.